Seismic performance of frames with passive energy dissipation steel slit plates - Ruiz, Daniel; Pimiento, Juan; Salas, Andrés (Revista Ingeniería de Construcción, 2014)
This paper evaluates two types of hysteretic passive energy dissipation devices (steel slit plates). These devices are low-cost and easy to build and install. The seismic performance of three structural models were studied with shake table tests: a frame without energy dissipation device and two frames with two types of steel slit plates. The models were instrumented with accelerometers, strain gages and LVDTs, and were subjected to two types of earthquakes signals: a regional earthquake and a near-field ground motion. The results of laboratory tests suggest that the frame with steel slit plates have up to 90% less seismic drift than the frame without rehabilitation. This is because steel slit plates dissipated a large portion of the input energy supplied by earthquakes and the damage to the parent structure was minimized.